Atividades do flumioxazin e matribuzin em dois tipos de solos em diferentes períodos de seca - OLIVEIRA, MAURÍLIO F. DE; Silva, Antônio A. da; Ferreira, Francisco Affonso; Firmino, Luís Eduardo; Sediyama, Carlos S. (Revista Ceres, 2015)
-